A comparison of midazolam and diazepam in premedication for upper gastrointestinal endoscopy - Hülya ÇETİNKAYA and Neşet KÖKTÜRK and İrfan SOYKAN and Mehtap ÖZDOĞAN and Şennur BERBER and Nuray KARAGÜLLE and Ali ÖZDEN (Turkish Journal of Gastroenterology, 2020)
-